2019
DOI: 10.3390/nano9111563
|View full text |Cite
|
Sign up to set email alerts
|

Layer by Layer Antimicrobial Coatings Based on Nafion, Lysozyme, and Chitosan

Abstract: The study focuses on the development of a new family of layer-by-layer coatings comprising Nafion, lysozyme and chitosan to address challenges related to microbial contamination. Circular dichroism was employed to gain insights on the interactions of the building blocks at the molecular level. Quartz crystal microbalance tests were used to monitor in real time the build-up of multilayer coatings, while atomic force microscopy, contact angle and surface zeta potential measurements were performed to assess the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 47 publications
0
17
0
Order By: Relevance
“…As in several systems prepared via a layer by layer approach [37][38][39][40], the proposed surface modification proceeds with a simple electrostatic deposition, in this case on an APTES functionalized glass surface. The approach proposed here may offer several advantages: CuS NP are easy to prepare and almost inexpensive, especially when compared to noble metal nanoparticles or synthetic antibacterial moieties that have to be grafted to surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…As in several systems prepared via a layer by layer approach [37][38][39][40], the proposed surface modification proceeds with a simple electrostatic deposition, in this case on an APTES functionalized glass surface. The approach proposed here may offer several advantages: CuS NP are easy to prepare and almost inexpensive, especially when compared to noble metal nanoparticles or synthetic antibacterial moieties that have to be grafted to surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…2a-d indicate the spherical nature of CU03D, CU25D, CU50D and CU100D nanoparticles with diameters in the range of 10-15 nm. Previous studies suggested that the size of C-dots derived from CA/urea mixtures varies from 2 to 11 nm [31][32][33][34][35][36][37][38][39][40][41][42][43]. The XRD patterns of the four members of D-series (Fig.…”
Section: Resultsmentioning
confidence: 88%
“…The results show that the growth of the film mass is linear for the PLL/Nafion deposition, which is in agreement with the limited data available in the literature concerning the growth mode previously observed for other pairs of polycation/Nafion. 9 , 10 However, the polymer mass increment during the deposition step was higher for the Nafion layer than for the PLL one.…”
Section: Resultsmentioning
confidence: 96%